Pendidikan Agama Islam pada Remaja dalam Konteks Kemiskinan Pedesaan - Zahra, Dewi; Hayati, Nur Rohmah (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
Religious education plays an important role in shaping adolescents’ character and spiritual resilience, especially during a developmental phase that is vulnerable to social and economic influences. However, in the context of poor rural communities, the implementation of religious education often faces various limitations. This study aims to examine the implementation of religious education among adolescents in Sucenjurutengah Village, Bayan District, Purworejo Regency, and to identify the factors influencing it. The method used is a descriptive qualitative approach with a case study design. The research subjects consist of 10 adolescents, 5 parents, and 3 religious leaders selected purposively. Data collection techniques include observation, in-depth interviews, documentation, and field notes. Data analysis is carried out through data reduction, data display, and conclusion drawing using triangulation. The findings show that structural poverty significantly affects the low participation of adolescents in non-formal religious education. The main obstacles include involvement in family economic activities, limited educational facilities, and the influence of digital entertainment. Nevertheless, adolescents still demonstrate relatively good religious awareness and potential for development. Therefore, a contextual, collaborative, and socially just approach is needed